Relational egalitarianism and the COVID-19 pandemic - Tolentino, Jacqueline Marie J. (2020)
The current COVID-19 pandemic has called for unprecedented measures to contain it and, as such, has reinforced and produced complex and intertwining health and non-health inequalities. I take the perspective of relational egalitarianism and argue that these inequalities are not only issues of public health and economics but also of social justice. I thus aim to construct a relational egalitarian framework to examine how and why the inequalities of COVID-19 are unjust and to work out what structural changes and processes might be required to justly respond to these inequalities.
Keywords: Covid-19 (Disease); COVID-19 pandemic; Public health; Equal rights; Equality; Social justice